Using story reading and explicit instruction in the vocabulary acquisition of kindergarten children - Singzon, Pamela D. (2008)
This research investigated the relationship of children's literature with the vocabulary acquisition of kindergarten children. A quasi-experimental study was conducted involving three kindergarten classes from a public school in Diliman, Quezon City. The medium of instruction used during the study was English. Two groups were exposed to different teaching methods of story telling while the third group utilized explicit instruction as the method of teaching. It was determined that there was a significant difference in the vocabulary acquisition of the kindergarten students. The outcome of the study confirmed that story reading with prereading is the most effective method inthe vocabulary acquisition of kindergarten students.
Thesis (M.A. Teaching in Early Grades, K-2)--University of the Philippines, Diliman.
Keywords: Storytelling in education; Language acquisition -- Philippines -- Quezon City; Reading (Kindergarten) -- Philippines -- Quezon City; Kindergarten -- Philippines -- Quezon City; Children -- Philippines -- Quezon City -- Language